World Risk Society and Ulrich Beck’s Manufactured Uncertainties - Antonilli, Andrea (Italian Sociological Review, 2022)
The aim of this contribution is to pursue Ulrich Beck’s line of thought with particular reference to the rise of the ‘world risk society’ triggered by globalization and by the metamorphosis of nature and risk features in early modernity. Globalized risk appears to be a feature specific to second modernity and a useful instrument for the interpretation of the social transformations now under way. Risks undergo a process of hardly reversible universalization: wherever produced, their distribution, and therefore their effects, will impact not only on a limited local dimension but will interest the whole global community. Speaking of world risk society means considering the extended range of the consequences coming from new risks which appear to be delocalized across space, time and societies, and to be incalculable and not subject to compensation. The inadequacy of the various branches of expert knowledge in foreseeing and confronting these new forms of risk sets in motion a series of paradoxical actions that appear in the spread of what Beck calls fabricated uncertainties, i.e., insufficiently thought-out decisions produced by organizations of knowledge in an attempt to contain those uncertainties already in existence; the effect of this is a failure to guarantee an on-going choice between a risky option and a safe one, but to select that option that may cause the least possible damage.[...]